Out of Many, One? Strasbourg's Ibrahim Decision on Article 6. Issue 6 (20th November 2017) - Goss, Ryan
Abstract: This case comment considers the European Court of Human Rights decision of Ibrahim v United Kingdom on 13 September 2016. Relying on Salduz v Turkey, the applicants claimed, largely unsuccessfully, that denial of access to a lawyer during police questioning, and subsequent admission into evidence of statements made in the course of that questioning, violated fair trial rights protected by Article 6 of the European Convention on Human Rights. The comment suggests that the decision's unusually emphatic statements about Article 6's 'internal structure' have consequences for assessing violations in future applications. Further, the decision creates greater room for public interest balancing in Article 6 cases. The decision may thus undermine the Article 6 guarantees.